Strategi Pengelolaan Limbah Bahan Berbahaya Dan Beracun (B3) Di Rumah Sakit Umum Daerah (RSUD) Ulin Kota Banjarmasin - Muhammad Zidan Alfito; Nasruddin Nasruddin (Geosfera: Jurnal Penelitian Geografi, 2025)
Hazardous and Toxic Waste (B3) is waste that contains hazardous or toxic materials which, due to their nature and/or concentration, quantity, either directly or indirectly, can pollute and/or damage the environment, endanger the environment, the health of humans and living creatures. others. Many industries do not realize that the waste they produce is included in the category of Hazardous and Toxic Waste (B3), so they easily release it into water bodies without processing, even though the waste produced can harm living creatures. The method used in this research is descriptive qualitative (Sidiq Khoiri, 2019). This research was conducted to obtain alternative problem solutions or answer problems faced when managing B3 waste in the Ulin Regional General Hospital (RSUD) Banjarmasin City. Management of hazardous medical waste (B3) is an important part of responsible and sustainable medical practice.  B3 medical waste includes materials such as syringes, expired medicines, dangerous chemicals, and biological waste with potential for infection. The volume of waste from the Ulin Regional General Hospital, Banjarmasin City in 2023, which produced the most B3 medical waste in March, was 10,918.31 kg, in September it was 8,082.29 kg, and in February it was 7,122.25 kg. In January - May, the most B3 medical waste was infectious waste, while in June - December it was infectious waste (COVID-19).